SOSIALISASI GERAK TERNAK SEJAHTERA KKN REGULER ANGK. V UNIM BONE DI DESA WAEMPUTTANGE KECAMATAN AMALI: GERAK TERNAK SEJAHTERA - Muh. Yusri; H. Sandi, S.Pd., M.Pd.; Herlisa; Nirmalasari; Mursalim; Septian Bayu Anggara; Risma; Andi Arya Saputra; Arisman L (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This activity is one of the flagship work programs of the Faculty of Agriculture and Animal Husbandry (FPP) by Regular KKN Batch V students of Muhammadiyah University of Bone in the form of community service activities that aim to provide information to the community through socialization, especially to livestock farmers in Waemputtange Village, Amali District, Bone Regency regarding methods or ways to improve the welfare of livestock farmers through increasing livestock productivity, livestock health, and sustainable livestock management such as the results of the livestock. The main target of this prosperous livestock movement socialization activity is the general public who are involved or not in the livestock sector in Waemputtange Village. This activity was carried out with direct presentation of material by KKN students. Based on the results of the activities that have been carried out, the participants, especially livestock farmers, were very enthusiastic about listening to the socialization material and played an active role during the question and answer process regarding increasing livestock productivity, livestock health, and sustainable livestock product management by livestock farmers that are appropriate and have the potential to be implemented in the Waemputtange Village environment. After the socialization activity of the prosperous livestock movement was held, the farmers gained a lot of new knowledge regarding the ease of raising livestock, increasing livestock productivity, maintaining the health of livestock and managing livestock and its results, so that the objectives of implementing this socialization by KKN students were successfully achieved.